Clinical chemistry, immunology and laboratory quality control : a comprehensive review for board preparation, certification and clinical practice - Dasgupta, Amitava, 1958-; Wahed, Amer (San Diego, CA : Elsevier, 2014)
All pathology residents must have a good command of clinical chemistry, toxicology, immunology, and laboratory statistics to be successful pathologists, as well as to pass the American Board of Pathology examination. This book presents core topics and detailed case studies that illustrate the application of clinical chemistry knowledge to everyday patient care and offers practical examples of how things function in the pathology clinic.
Chapter 1. Instrumentation and analytical methods -- chapter 2. Immunoassay platform and designs -- chapter 3. Pre-analytical variables -- chapter 4. Laboratory statistics and quality control -- chapter 5. Water, homeostasis, electrolytes, and acid-base balance -- chapter 6. Lipid metabolism and disorders -- chapter 7. Carbohydrate metabolism, diabetes, and hypoglycemia -- chapter 8. Cardiac markers -- chapter 9. Endocrinology -- chapter 10. Liver diseases and liver function tests -- chapter 11. Renal function tests -- chapter 12. Inborn errors of metabolism -- chapter 13. Tumor markers -- chapter 14. Therapeutic drug monitoring -- chapter 15. Interferences in therapeutic drug monitoring -- chapter 16. Drugs of abuse testing -- chapter 17. Challenges in drugs of abuse testing : magic mushrooms, peyote cactus, and designer drugs -- chapter 18. Testing for ethyl alcohol (alcohol) and other volatiles -- chapter 19. Common poisonings including heavy metal poisoning -- chapter 20. Pharmacogenomics -- chapter 21. Hemoglobinopathy -- chapter 22. Protein electrophoresis and immunofixation -- chapter 23. Human immunodeficiency virus (HIV) and hepatitis testing -- chapter 24. Autoimmunity, complement, and immunodeficiency -- chapter 25. Effect of herbal supplements on clinical laboratory test results.
Includes bibliographical references and index.
Keywords: Clinical chemistry; Clinical chemistry -- Case studies; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Clinical chemistry; Electronic books; Case studies